Redox and Nitrosative Signaling in Cardiovascular System: From Physiological Response to Disease - Pasquale Pagliaro (Frontiers Research Topics, 2019)
The role of ROS/RNS signaling in cardiovascular functions and diseases is increasingly emerging in the last decades. The involvement of ROS/RNS in the control of a large number of cardiovascular functions like the regulation of the vascular tone, the control of blood pressure or myocyte excitation-contraction coupling and force development has been broadly investigated and in part clarified. On the other hand, many efforts have been focused in clarifying the redox mechanisms involved in cardiovascular diseases like ischemia/reperfusion injury, diabetes-associated cardiovascular dysfunctions, atherosclerosis or hypertension, just to mention the major ones. However, in most cases the two levels of investigation remain separate and not interlaced, failing in the attempt to provide a unified vision of the pathophysiologic mechanisms of cardiovascular diseases. The major aim of the Research Topic has been to collect original papers and review articles dealing with the issue from basic to translation research point of views. The topic includes contributions that highlight different interesting aspects of cardiovascular biology with an integrated approach useful for the development of new ideas and advancements in the field of redox signaling in the control of normal cardiovascular functions and their disruption in diseases.